Strategic Management: Building Frame Work IT Governance In University Environment - Rijayana, Iwan; Aghnia Fadilah, Ratu; Putra Tarigan, Andy; Jonathan Sirait, Ganda; Kausar Riansyah, Haykal (International Journal of Psychosocial Rehabilitation, 2020)
IT-Governance Issues in Higher Education environment is not just a matter of website development, but involves the application and infrastructure are far more complex, as well as adequate management context. Because it is uncertain if an institution only buys applications and infrastructure, without adjustment of management, it is unlikely to succeed. This model can be considered in implementing IT-Governance IT Governance is a model such as COBIT, ITIL, COSO, ISO / IEEC, etc. All these models are usually nice to be developed within the company, but not necessarily the best when developed in the higher education environment. Trends and issues in tertiary education in Indonesia in recent years faced with the problem (1) loss of confidence in the benefits of higher education, (2) changing patterns of potential interest to students majoring in vocational; (3) increased competition among universities; (4) the cost of education very high; (5) the number of opening a community college which is geographically closer to students and low-cost, (6) the increasing concern for more effective education management